Vietnam : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper assesses the Poverty Reduction Strategy Paper of Vietnam, known as the Comprehensive Poverty Reduction and Growth Strategy (CPRGS). It is an action program to achieve economic growth and poverty reduction objectives. This paper reviews the objectives and tasks of socio-economic development and poverty reduction. The government of Vietnam takes poverty reduction as a cutting-through objective in the process of country socio-economic development and declares its commitment to implement the Millennium Development Goals and poverty reduction objectives.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet